Urgensi Pendidikan Kaum Perempuan pada Era Globalisasi: Telaah Pemikiran Siti Walidah - Ziana Maulida Savira; Muh Nur Islam Nurdin; Sutrisno Sutrisno (Nusantara: Jurnal Pendidikan Indonesia, 2023)
Social constructs have shifted women's participation in education. Differences in role and status have placed women at a disadvantage in accessing education. This research aims to describe the urgency of women's education in the era of globalization from the perspective of Siti Walidah. This research is a literature study that adopts a descriptive method with a critical approach. Data processing is done with the framework proposed by Miles and Huberman. The results show that Siti Walidah personally applies Al-Ashr theology where in life she must make the best use of time. Siti Walidah's educational ideas refer to the concept of "Catur Pusat" which combines the four elements: education in the family, school, community, and education in places of worship. This catur pusat concept forms an integrated whole. This thinking led Siti Walidah to pioneer the movement as evidenced by the establishment of Sopo tresno, giving lessons to women from Kauman to learn to read the Qur'an through Wal 'Ashri, and establishing the Maghribi school. Siti Walidah's thoughts and movements that place women as pioneers for advancing civilization are very important and can become a paradigm for women facing the challenges of the globalization era.